2009
DOI: 10.1510/icvts.2009.202150
|View full text |Cite
|
Sign up to set email alerts
|

Experimental selective sympathicotomy (ramicotomy) and sympathetic regeneration

Abstract: Ramicotomy is a surgical procedure, with less adverse effects than conventional sympathectomy, however, it was abandoned due to the high recurrence rate. Twenty-eight pigs underwent bilateral videothoracoscopic ramicotomy and were divided into five groups. The animals were sacrificed at 15th, 45th, 90th, 135th and 180th postoperative days (POD). The segments were removed and evaluated for macroscopic regeneration and histological analysis. The data were compared to the control group of 10 intact segments of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
0
8
1
Order By: Relevance
“…The present study identified no significant differences with respect to the inflammatory process of clipping compared to section. It is speculated the possibility of not triggering the process of Wallerian degeneration 19 , what this paper does not show. Here was no significant the difference between the groups regarding the inflammatory process and its degree.…”
Section: Assessment Of Inflammation and Necrosiscontrasting
confidence: 64%
See 1 more Smart Citation
“…The present study identified no significant differences with respect to the inflammatory process of clipping compared to section. It is speculated the possibility of not triggering the process of Wallerian degeneration 19 , what this paper does not show. Here was no significant the difference between the groups regarding the inflammatory process and its degree.…”
Section: Assessment Of Inflammation and Necrosiscontrasting
confidence: 64%
“…Regarding to collagen, Oliveira et al 19 noted elevated levels of it in both types, I and III, increasing up to its peak point, on 135 th day, postoperatively.…”
Section: Assessment Of Inflammation and Necrosismentioning
confidence: 98%
“…Interestingly, T3 ramicotomy resulted in a lower rate of compensatory sweating compared to T3 sympathetic clipping, and there was no significant difference in the rate of satisfaction for palmar hyperhidrosis treatment (14). Furthermore, due to the high rate of ramicotomy recurrence but less adverse effects than conventional sympathectomy, sympathetic regeneration is the key factor associated with the recurrence of symptoms after ramicotomy in humans (15). In Kim et al study, video-assisted thoracoscopic (VAT) T2 sympathetic clipping and VAT ramicotomy were performed in patients with craniofacial hyperhidrosis to reduce the incidence of compensatory sweating and were shown to be significantly lower than T2 sympathetic clipping despite the high operating failure rates (16).…”
Section: Discussionmentioning
confidence: 98%
“…Thoracoscopic ramicotomy, which involves cutting only the rami communicantes (RCs), has a theoretical advantage over other methods and involves a less‐aggressive surgical approach for treating hyperhidrosis (Kim et al, ; Lee et al, ). However, the high recurrence rate could necessitate abandonment of this approach (Oliveira et al, ).…”
Section: Introductionmentioning
confidence: 99%